STUDI EKSPERIMEN PENGARUH KEKUATAN MATERIAL KOMPOSIT HGM, EPOXY DAN SERAT DAUN NANAS TERHADAP KEKUATAN TARIK DAN IMPAK - Muhammad Alfarizi; Boy Rollastin; Sukanto Sukanto (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Pineapple leaf fiber is one of the plantation wastes that is rarely processed and has a low selling value, Therefore, pineapple leaf fiber is used as a reinforcement for composite materials with an epoxy as a matrix and 16% filler material in the form of Hollow Glass Microsphere which is expected to produce renewable materials that can increase the selling value of the waste.. This study aims to determine how the effect of composite composition on tensile strength and impact of several parameters used. The testing process carried out is tensile test and charpy impact test with matrix and fiber volume fractions, namely, 74%:10%, 12.5%:71.5%  and 15%:69%  with horizontal and vertical fiber directions. Based on this study, specimens with a fiber fraction thickness of 15% with a vertical direction resulted in an average tensile strength of 84.83 MPa and the highest average impact strength was obtained in specimens with the same parameters is 0.1367 J/mm².